Phototherapy up-regulates dentin matrix proteins expression and synthesis by stem cells from human-exfoliated deciduous teeth - Turrioni, Ana Paula S. [UNESP]; Basso, Fernanda G. [UNESP]; Montoro, Liege A. [UNESP]; Almeida, Leopoldina de Fatima D. de [UNESP]; Souza Costa, Carlos A. de [UNESP]; Hebling, Josimeri [UNESP] (Elsevier B.V., 2014)
Objectives: The aim of this study was to evaluate the effects of infrared LED (850 nm) irradiation on dentin matrix proteins expression and synthesis by cultured stem cells from human exfoliated deciduous teeth (SHED).Methods: Near-exfoliation primary teeth were extracted (n = 3), and SHED cultures were characterized by immunofluorescence using STRO-1, CD44, CD146, Nanog and OCT3/4 antibodies, before experimental protocol. The SHEDs were seeded (3 x 10(4) cells/cm(2)) with DMEM containing 10% FBS. After 24-h incubation, the culture medium was replaced by osteogenic differentiation medium, and the cells were irradiated with LED light at energy densities (EDs) of 0 (control), 2, or 4 J/cm(2) (n = 8). The irradiated SHEDs were then evaluated for alkaline phosphatase (ALP) activity, total protein (TP) production, and collagen synthesis (SIRCOL (TM) Assay), as well as ALP, collagen type I (Col I), dentin sialophosphoprotein (DSPP), and dentin matrix acidic phosphoprotein (DMP-1) gene expression (qPCR). Data were analyzed by Kruskal-Wallis and Mann-Whitney tests (alpha = 0.05).Results: Increased ALP activity and collagen synthesis, as well as gene expression of DSPP and ALP, were observed for both EDs compared with non-irradiated cells. The ED of 4 J/cm(2) also increased gene expression of COL I and DMP-1.Conclusions: In conclusion, infrared LED irradiation was capable of biostimulating SHEDs by increasing the expression and synthesis of proteins related with mineralized tissue formation, with overall better results for the energy dose of 4 J/cm(2).Clinical significance: Phototherapy is an additional approach for the clinical application of LED in Restorative Dentistry. Infrared LED irradiation of the cavity's floor could biostimulate subjacent pulp cells, improving local tissue healing. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Dentin; Odontoblasts; Phototherapy; Protein expression; Pulp biology; Stem cells